Reduction Right Fulfillment of the Sentence Against Class IIB Convicts Sosaiu Tidore City of Tidore Islands - Hasmiah Hasmiah (Peneliti.net, 2023)
This study aims to provide an empirical description of the reduction right fulfillment of the sentence against convicts at the Sosaiu Tidore Class IIB Detention Center. City of Tidore Islands. Reduction right fulfillment of the sentence is a mandatory right that needs to be protected and fulfilled by every officer who has authority over this matter. This hope is important to study in scientific research to find out how far the implementation of these regulations regulates the rights of convicts. The design of this study uses descriptive qualitative assisted by data collection through field observations, documentation studies, and interviews with a number of informants who are considered capable and wisely understand the object of this research. Because the problems are complex and require an in-depth understanding of meaning, the results of the interviews become information that must be interpreted to produce a conclusion in this thesis. The results show that the fulfillment of the rights of every convict in reducing his sentence in the Class IIB Detention Center has been carried out based on the applicable regulations, however, there are several inhibiting factors in the process towards that direction, including: HR issues in technology-based administrative management, readiness for prison administration and there are regulations that do not have clarity yet in the provision of recommendations if inmates give power of attorney to other people or through Class IIB Soasiu Tidore Detention Center officers.